Myoclonus and hypercalcemia in a dog with poorly differentiated lymphoproliferative neoplasia - Hare, Cassia H. Z. (J Vet Intern Med, 2018)
A 1‐year, 8‐month‐old Rhodesian Ridgeback was presented with obtundation, ambulatory tetraparesis, and myoclonus. Initial clinical findings included ionized hypercalcemia with an apparent marked increase in parathyroid hormone, thrombocytopenia, and nonregenerative anemia. Low numbers of circulating atypical cells were noted on blood film evaluation. Brain magnetic resonance imaging identified an extra‐axial contrast enhancing subtentorial lesion, and cerebrospinal fluid (CSF) analysis documented a marked atypical lymphocytic pleocytosis. Flow cytometry performed on the CSF demonstrated expression of only CD45, CD90, and MHC class II, with Pax5 positivity on subsequent immunohistochemistry. The final diagnosis was of B‐cell lymphoblastic lymphoma or acute leukemia, given the distribution of disease and the presence of significant bone marrow infiltration alongside an aggressive clinical course. The unusual immunophenotype of the neoplastic cells and hypercalcemia presented antemortem diagnostic challenges, highlighting the need for a multidisciplinary approach and caution in the interpretation of clinical abnormalities in cases with multiple comorbidities.